Математичне моделювання просторового розподілу сукупності корисних копалин методами інтерлінації матриць-функцій - Чорна, О. С. (ХНУРЕ, 2019)
У дисертаційній роботі запропоновано рішення актуальної науково-практичної задачі розробки математичної моделі просторового розподілу сукупності корисних копалин методами інтерлінації матриць функцій. В роботі розроблені і досліджені методи відновлення матричної функції від трьох змінних між заданою системою ліній, які описують задану систему свердловин; з цього методу як частинний випадок випливає метод відновлення функції трьох змінних між системою заданих ліній, що описують систему свердловин методами поліноміальної, глобальної та сплайн-інтерлінації функцій трьох змінних. Сформульовані і доведені теореми про те, що оператори інтерлінації матричних функцій трьох змінних мають сліди цієї матричної функції в точках кожної із заданих лінії. У роботі проведено теоретичне порівняння методів інтерлінації матричних функцій, і вироблені рекомендації про те, які допоміжні функції в операторах матричних функцій краще використовувати. Ефективність запропонованих моделей перевірено за допомогою обчислювального експерименту на основі створених дисертантом програм, які реалізують вказані вище методи побудови математичних моделей. Запропоновано подальший розвиток методів відновлення функції трьох змінних між системою заданих ліній, що описують систему похилих свердловин методами поліноміальної, глобальної та сплайн-інтерлінації функцій трьох змінних. У роботі проведено обчислення запасів корисних копалин за даними з кернів похилих свердловин. In dissertation work the decision of the actual scientific and practical task of development of a mathematical model of spatial distribution of mineral resources by methods of interming of matrices of functions is proposed. In this work, methods for the restoration of a matrix function from 3 variables between a given system of lines that describe a given well system are developed and investigated; From this method, as a partial case, follows the method of restoring the function of 3 variables between the system of given lines describing the well system using polynomial, global, and spline-interlination functions of 3 variables. The research methods are based on the use of the theory of functional analysis (for the study and development of methods for assessing mineral reserves), computational mathematics (for obtaining the form of basis polynomials (or splines) on the system of spatial noncontinuous curves), the theory of approximation of the functions of several variables using the interpolation of functions (for the construction of mathematical models for restoring the distribution of the density of the investigated object according to the data of the spatial curves). The basis of the numerical implementation is the interlination of the functions of 3 variables using the data of the system of spatial non-intersecting curves in vertical planes; SCM MathCad 15 when testing the developed algorithms.The interlacing operator proposed in the dissertation can calculate the value of a function from three variables between curves if the information about the function is given by the traces in these curves. In this case, if the distribution is determined by a continuous function, which is a polynomial of degree for variables and for each, then the interlocation operator will definitely restore such a function. The scientific results of the dissertation work are the further development of the methods of interlinational functions. The practical significance of the obtained theoretical results of the dissertation work is confirmed by the application of the theory of interlination of functions of 3 variables to the solution of the problems of restoring the spatial distribution of the density of objects between the system of spatial curves in vertical planes. The mathematical models and methods of working out the tasks of restoration of the density distribution of the aggregate of minerals as trivial functions of the methods of the interpolation of the functions of the three variables into the system of invincible spatial criminal permissions are developed. The modified modifications of methods allow, based on information about the presence of objects, to restore the corresponding layer or other minerals. The practical significance of the results of confirmation of their implementation.
Keywords: математичне моделювання; просторовий розподіл; методи інтерлінації; матриці-функції; сукупність корисних копалин; похилі свердловини; mathematical modeling; spatial distribution; methods of interlination; matrix-function; aggregate of minerals; inclined wells, functions of three variables